0948 (An) Exercise in diagnosing (a rare cause of) double vision. (1st December 2017) - Stevenage, Mary; Theochari, Evangelia; Johnson, Declan; Warner, Graham
Abstract : Parinaud first described the paralysis of vertical gaze due to mesencephalon damage in 1883. We report a rare cause of Parinaud's syndrome. A 44 year old female presented with a two-day history of acute onset double vision and unsteadiness following a night out dancing. Eighteen months prior to this, she developed new mild and short-lived episodic headaches associated with photopsia, which increased in frequency after taking up a dancing class. Additionally, she experienced subungal pain following exertion. Neurological examination revealed up-gaze paralysis with partial convergence and slightly left lateral gaze limitation. Brain MRI showed acute and subacute infarcts in multiple territories, suggestive of a vasculitic or embolic aetiology. An echocardiogram revealed a large left atrial myxoma, which was subsequently surgically excised. Atrial myxoma represents a rare case of embolic stroke in a young otherwise well adult. The temporal relation of symptoms with exercise gave a clue in the history for the cardiac aetiology rather than an inflammatory process. The migrainous features could be explained by cerebral hypoperfusion or microemboli triggering cortical spreading depression and the subungual pain could also reflect similar phenomena in the extremities. The anatomical localisation of Parinaud's various descriptions of clinical presentations is discussed in detail.